Ecosystemic Approaches to Extractive Business and Human Rights Issues - Roy Grégoire, Étienne; Anzueto, Marc-André; Campbell, Bonnie; Séguin, Mélisande; Tapias Torrado, Nancy (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2023)
The article by Étienne Roy Grégoire, Marc-André Anzueto, Bonnie Campbell, Mélisande Séguin and Nancy R Tapias Torrado uses the concept of an ‘extractive normative ecosystem’ to account for the interactions between the various norms, discourses and policies governing the relationship between extractive industries and local communities. It argues that the exploitation of natural resources significantly alters social relations and exacerbates the risks of human rights violations, particularly in the context of globalisation. The article critiques traditional approaches to Corporate Social Responsibility (CSR) and Business and Human Rights (BHR), and highlights the need for an ecosystem approach to understand the complex relationships between different regulatory regimes, including state laws, indigenous legal systems and international law. The text is divided into four sections: the theoretical implications of the ecosystem paradigm, recent legal developments in business and human rights due diligence legislation in Europe and Canada, the potential of applying an ecosystemic approach to the extractive sector, and a conclusion highlighting the challenges faced by communities affected by extractivism.